2022
DOI: 10.1111/ajo.13500
|View full text |Cite
|
Sign up to set email alerts
|

eLearning significantly improves maternity professionals’ knowledge of the congenital cytomegalovirus prevention guidelines

Abstract: Aims: Cytomegalovirus (CMV) is a preventable cause of neurodevelopmental disability. Australian guidelines recommend that pregnant women are informed about CMV to reduce their risk of infection; however, less than 10% of maternity health professionals routinely provide prevention advice. The aim was to develop and evaluate the effectiveness of an eLearning course for midwives to improve knowledge and confidence about CMV. Materials and Methods: Participants undertaking the course between March and November 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Knowledge of CMV and its mode of transmission is the cornerstone of primary prevention, enabling women of childbearing age and in early pregnancy to apply adapted hygienic measures to avoid CMV primary infection or re-infection [20]. Despite an evolution in awareness over the last decade, the most recent studies still show significant gaps in the knowledge of pregnant women [21][22][23], which considerably reduces the effectiveness of primary prevention. At the same time, constant progress in CMV vaccines may provide a promising option to prevent maternal infections during pregnancy in the near future.…”
Section: Primary Prevention: To Reduce the Risk Of Maternal Primary I...mentioning
confidence: 99%
See 4 more Smart Citations
“…Knowledge of CMV and its mode of transmission is the cornerstone of primary prevention, enabling women of childbearing age and in early pregnancy to apply adapted hygienic measures to avoid CMV primary infection or re-infection [20]. Despite an evolution in awareness over the last decade, the most recent studies still show significant gaps in the knowledge of pregnant women [21][22][23], which considerably reduces the effectiveness of primary prevention. At the same time, constant progress in CMV vaccines may provide a promising option to prevent maternal infections during pregnancy in the near future.…”
Section: Primary Prevention: To Reduce the Risk Of Maternal Primary I...mentioning
confidence: 99%
“…However, the results of numerous studies conducted worldwide have shown that the practices of health professionals regarding CMV information and prevention differ considerably from one professional to another [21,72]. In order to understand the reasons for these divergent practices, some authors have looked at the training of future health professionals as well as the place allocated to CMV education in academic curriculum [23,73]. One study reported that gaps were identified early in the training of future physicians.…”
Section: Effectiveness Of Educational Interventionsmentioning
confidence: 99%
See 3 more Smart Citations